The Six Value Of Socio-Ecopreuneur Lombok Eco Flea Market Untuk Pemberdayaan Petani Dan Pengrajin Lokal Di Kuta Lombok Tengah - Komala, Rina; ., Khairunnisa; Aryani, R. Ayu Ida (Income : Digital Business Journal, 2023)
Lombok Eco Free Market is a collaborative ecopreneur community located in Kuta Village, Central Lombok which provides a place to help and empower local farmers and craftspeople around Kuta, Central Lombok to develop businesses and improve their standard of living. In running its business Lombok Eco Flea Market uses 6 (six) principles as a branding strategy, namely: Empowering Women and Communities, Conscious Shopping or Fair Trade, Circular Economy, Earth Friendly Products, Local Wisdom and digital-marketing and is the main requirement for vendors who want to join the Lombok Eco Flea Market. These principles are in line with the policy of the West Nusa Tenggara Provincial government in the West Nusa Tenggara Provincial government's social safety net program, namely economic stimulus and recovery due to Covid-19 by defending and buying local products so that Micro, Small and Medium Enterprises in West Nusa Tenggara Province can actively operate again . This research is a qualitative research that aims to analyze the six main principles of Lombok Eco Flea Market in realizing its mission to empower and improve the welfare of local farmers and craftsmen in Kuta, Central Lombok through ecopreneurs.